Criticizing Global Governance
XIV, 280 p.
Keywords: The essays in this collection seek to reflect on global governance and to provide a better critical understanding of the various practices that fall under its rubric. The first part challenges the concept of global governance, the second part focuses on organizational and institutional aspects, and the last part examines the rule systems implemented by global governance practices. The vocabulary of (global) governance has become a serious contender to imagine world order in the post cold war world. Using different strategies of critique, the contributors argue that global governance denotes a political vocabulary where acts of definition themselves are political moves.